Petersburg Press London 1968-1976. - Cornwall-Jones, Paul; Lindsay, Véra; Petersburg Press, London (Paris : Galerie de Paris, 1976)
Dine, Jim ; Duchamps, Marcel ; Hamilton, Richard ; Hockney, David ; Johns, Jasper ; Kitaj, R.B. ; Moore, Henry ; Oldenburg, Claes ; Rosenquist, James ; Roth, Dieter ; Stella, Frank ; Tobey, Mark
Petersburg Press London 1968-1976, Galerie de Paris, Paris, avril - juin 1976
boek